2019
DOI: 10.1002/hed.25944
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant therapies in the management of medication‐related osteonecrosis of the jaws: Systematic review

Abstract: Background We investigated the efficacy of hyperbaric oxygen (HBO), low‐intensity laser (LIL), and platelet‐rich plasma (PRP) in the management of medication‐related osteonecrosis of the jaws (MRONJ). Methods A literature search was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses statement. Two examiners independently assessed eligibility and risk of bias and extracted data. Results There was improvement in 75.6% of the 41 patients submitted to HBO, with posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 72 publications
(378 reference statements)
0
25
0
4
Order By: Relevance
“…102 However, there is no clear guidance on how to determine the surgical plan for patients in stages 2 and 3 for whom conservative treatment was ineffective, so surgical treatment is therefore advocated. [103][104][105] However, the type of recommended surgical intervention, including preservation or segmental resection of the jaw, determination of the incisal margin of safety, soft tissue management and selection of functional reconstruction, is not clear.…”
Section: Therapy For Mronjmentioning
confidence: 99%
See 2 more Smart Citations
“…102 However, there is no clear guidance on how to determine the surgical plan for patients in stages 2 and 3 for whom conservative treatment was ineffective, so surgical treatment is therefore advocated. [103][104][105] However, the type of recommended surgical intervention, including preservation or segmental resection of the jaw, determination of the incisal margin of safety, soft tissue management and selection of functional reconstruction, is not clear.…”
Section: Therapy For Mronjmentioning
confidence: 99%
“…123,124 Therefore, LIL has become an effective adjuvant therapy for MRONJ and is expected to become an alternative therapy. 104 Platelet-rich plasma (PRP), an autologous source of growth factors, has been successfully used in bone regeneration and soft tissue healing. 126,127 PRP can produce high concentrations of human platelets containing a variety of growth factors.…”
Section: Oncologymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have investigated novel approaches for MRONJ treatment, including hyperbaric oxygen therapy (Freiberger et al, 2012), platelet-rich plasma (Adornato et al, 2007;Curi et al, 2011), low-intensity laser irradiation (Favia et al, 2018;Scoletta et al, 2010), parathyroid hormones (Cheung and Seeman, 2010;Sim et al, 2020), bone morphogenetic proteins (Park et al, 2017), plasma rich in growth factors (Mozzati et al, 2012), pentoxifylline and tocopherol (Heifetz- Li et al, 2019), and cell therapy (Tables 2 and 3). Of these, no treatment modality is widely accepted (De Souza Tolentino et al, 2019). Sim et al (2020) demonstrated the promising therapeutic effects of teriparatide, which is a parathyroid hormone, against MRONJ in a randomized controlled clinical trial.…”
Section: Conventional and Novel Treatment Strategies For Mronjmentioning
confidence: 99%
“…ORN' nin tanımı ve sınıflandırması yıllar içinde değişiklik göstermiş, 1,2 ve çene osteonekrozu ile ilgili yeni tedavi alternatifleri gündeme gelmiştir. 3 Baş-boyun bölgesinden radyoterapi almış hastalarda çenelerde osteoradyonekroz gelişimini önlemek, enfeksiyona olan yatkınlığı azaltmak, damarlanması kötü olan dokuları sınırlandırmak ya da semptomları azaltmak için farklı yaklaşımlar ve tedavi protokolleri önerilmiştir. 4 Radyoterapi sonrasında dokunun rejenerasyon kapasitesini arttırmak amacıyla enflamasyonu baskılayarak iyileşmeyi desteklemek ve/veya enfeksiyöz tablonun gelişimini önlemek için kullanılan tedavi protokolleri tıbbın her alanında olduğu gibi ağız diş ve çene cerrahisi pratiğinde de sıklıkta kullanılmaktadır.…”
Section: Gereç Ve Yöntemunclassified